The Use of ICT in the Implementation of Student-Centered Learning (SCL) - Hafizoah, Kassim; Zuraina, Ali (Universiti Kebangsaan Malaysia, 2007)
As one of the new teaching approaches, Student-Centered Learning (SCL) has been proven to be effective in its ability to teach students. At Universiti Malaysia Pahang (UMP), the implementation of SCL is being strictly emphasized to ensure that students “…are responsible for their learning in which they can construct their learning by actively seeking their own information” (Abdullah,2005). On the other hand, UMP places emphasis on the utilization of its vastly equipped multimedia and digital infrastructure to the optimal level particularly in the teaching and learning process. Hence, the aim of this paper is to investigate the effectiveness of integrating ICT into the implementation of SCL in language classes especially through the use of Internet and Microsoft Office PowerPoint. Thus, the questions that we address in the study are: (i) Can the utilization of the Internet and PowerPoint enhance students’ learning through SCL? (ii)What are the implications of using these two ICT features in the SCL environment in language learning? The primary sources of the data are obtained from interview, questionnaire, class observation and learning-teaching activities which were gathered in UMP.